TINJAUAN PENERAPAN MANAJEMEN RISIKO DI UNIT FILING RSUD Dr. MOEWARDI - Bayu Aji Santoso; Sri Sugiarsi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
Based on preliminary survey at RSUD Dr. Moewardi who are at risk of being in the filing unit: filing officers may be exposed to cough disease if taking or deciding DRM without using masks, filing unit officers may be dropped or slipped when the medical record shooting is on a high shelf, in addition to filing units may be struck document record Medical and even some units of old filing units often found back pain due to up and down stairs to retrieve medical record documents. The purpose of this study was to determine the application of risk management in the hospital filing unit RSUD Dr. Moewardi.The type of research is descriptive with qualitative approach. The research methodology is observation and structured interview. The definition of concept in this research, factor management, factor control, risk control and control, risk attitude and monitoring. Research subjects are filing unit officer, medical record quality coordinator, filing unit coordinator and. The object of research is the filing unit RSUD Dr. Moewardi. Research result. In Dr. Moewardi is done internally, the risk factor in the filing unit is the most prominent is the risk of falling due to the high medical record rack, the attitude of the risks that occurred in the filing unit is to make incident reports and held the meeting, Monitoring carried out by the unit. Units of archiving.